2018
DOI: 10.3354/meps12645
|View full text |Cite
|
Sign up to set email alerts
|

Phases of microalgal succession in sea ice and the water column in the Baltic Sea from autumn to spring

Abstract: The phytoplankton biomass during the cold-water season (October−May) in the Baltic Sea is low compared to the warm-water season (June-September). However, the sea ice is a habitat for diverse assemblages in polar and subpolar areas. These areas, including the Baltic Sea, are subject to changing environmental conditions due to global warming, and temporal and spatial studies are required to understand changes in the processes organisms are involved in. We delineated the microalgal succession in the northern Bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 91 publications
1
49
0
Order By: Relevance
“…Analysis of 286 NCBI 18S rRNA databases (Table S1, Supplementary methods) that represent HTS studies conducted in various seas and oceans (e.g. Celussi et al 2018;Enberg et al 2018;Edgcomb et al 2011;Flaviani et al 2018;Hassett et al 2017;Pearman et al 2017;Stern et al 2015) identified that the fungi comprised 1.3% of all eukaryotic sequences from marine environmental datasets. Many fungal sequences from this study were only classifiable to higher taxonomic levels (Figure 3), consistent with other published findings (Comeau et al 2016, Nagano et al 2017, Picard 2017), suggesting either novel lineages and/or under-populated reference databases.…”
Section: Marine Fungal Community Analysis Using 18s Rrna Genesmentioning
confidence: 99%
“…Analysis of 286 NCBI 18S rRNA databases (Table S1, Supplementary methods) that represent HTS studies conducted in various seas and oceans (e.g. Celussi et al 2018;Enberg et al 2018;Edgcomb et al 2011;Flaviani et al 2018;Hassett et al 2017;Pearman et al 2017;Stern et al 2015) identified that the fungi comprised 1.3% of all eukaryotic sequences from marine environmental datasets. Many fungal sequences from this study were only classifiable to higher taxonomic levels (Figure 3), consistent with other published findings (Comeau et al 2016, Nagano et al 2017, Picard 2017), suggesting either novel lineages and/or under-populated reference databases.…”
Section: Marine Fungal Community Analysis Using 18s Rrna Genesmentioning
confidence: 99%
“…4 weeks during winter 2019. Microalgal studies in winter have concentrated on pelagic and sea-ice algae (e.g., Edgar et al, 2016;Enberg et al, 2018), which prevents comparing our results, but we speculate that low water temperature that always occurs during winter and wind-induced waves due to the lack of ice are cumulative stressors (Morin et al, 2015) that make species more vulnerable during ice-free winters. Thus, ice cover seems to be needed to protect high benthic diversity in winter.…”
Section: Discussionmentioning
confidence: 93%
“…The RCC5270 metabarcodes were only observed in the Arctic Ocean and in the Baltic Sea from ice and water samples as well from algal aggregates collected from the deep-sea floor (Figure 5A-B). Metabarcodes identical to the sequence of RCC5270 were particularly abundant in three datasets (Table 1) from the Polarstern expedition in the Central Arctic Ocean (Rapp et al, 2018), from the Nares strait, the northernmost outflow gateway of Baffin Bay (Kalenitchenko et al, 2019) and from the Gulf of Finland (Baltic Sea) (Enberg et al, 2018). At the latter location, which corresponds to the region from which C. birgeri was initially described, metabarcodes identical to the RCC5270 sequence first appeared in February in the ice where they peaked in early March and then increased massively in the water column one month later, representing up to 70% of the metabarcodes at the time the ice melted in mid-April (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…B) Zoom on the North Pole region. C) Maximum fraction of RCC5270 metabarcodes (excluding Metazoa) as a function of date in the Gulf of Finland (Baltic Sea) in ice and water (Enberg et al, 2018).…”
Section: Resultsmentioning
confidence: 99%